Rats bred for high anxiety exhibit distinct fear‐related coping behavior, hippocampal physiology, and synaptic plasticity‐related gene expression. Issue 10 (17th April 2019) - Widman, Allie J.; Cohen, Joshua L.; McCoy, Chelsea R.; Unroe, Keaton A.; Glover, Matthew E.; Khan, Anas U.; Bredemann, Teruko; McMahon, Lori L.; Clinton, Sarah M.
Abstract: The hippocampus is essential for learning and memory but also regulates emotional behavior. We previously identified the hippocampus as a major brain region that differs in rats bred for emotionality differences. Rats bred for low novelty response (LRs) exhibit high levels of anxiety‐ and depression‐like behavior compared to high novelty responder (HR) rats. Manipulating the hippocampus of high‐anxiety LR rats improves their behavior, although no work to date has examined possible HR/LR differences in hippocampal synaptic physiology. Thus, the current study examined hippocampal slice electrophysiology, dendritic spine density, and transcriptome profiling in HR/LR hippocampus, and compared performance on three hippocampus‐dependent tasks: The Morris water maze, contextual fear conditioning, and active avoidance. Our physiology experiments revealed increased long‐term potentiation (LTP) at CA3–CA1 synapses in HR versus LR hippocampus, and Golgi analysis found an increased number of dendritic spines in basal layer of CA1 pyramidal cells in HR versus LR rats. Transcriptome data revealed glutamate neurotransmission as the top functional pathway differing in the HR/LR hippocampus. Our behavioral experiments showed that HR/LR rats exhibit similar learning and memory capability in the Morris water maze, although the groups differed in fear‐related tasks. LR rats displayed greater freezing behavior in the fear‐conditioning task, and HR/LR rats adopted distinct behavioral strategies in the active avoidance task. In the active avoidance task, HRs avoided footshock stress by pressing a lever when presented with a warning cue; LR rats, on the other hand, waited until footshocks began before pressing the lever to stop them. Taken together, these findings concur with prior observations of HR rats generally exhibiting active stress coping behavior while LRs exhibit reactive coping. Overall, our current findings coupled with previous work suggest that HR/LR differences in stress reactivity and stress coping may derive, at least in part, from differences in the developing and adult hippocampus.